Structural proteins of Enterococcus faecalis bacteriophage ϕEf11 - Stevens, Roy H. (Bacteriophage, 2016)
ϕEf11, a temperate Siphoviridae bacteriophage, was isolated by induction from a root canal isolate of Enterococcus faecalis. Sequence analysis suggested that the ϕEf11 genome included a contiguous 8 gene module whose function was related to head structure assembly and another module of 10 contiguous genes whose products were responsible for tail structure assembly. SDS-PAGE analysis of virions of a ϕEf11 derivative revealed 11 well-resolved protein bands. To unify the deduced functional gene assignments emanating from the DNA sequence data, with the structural protein analysis of the purified virus, 6 of the SDS-PAGE bands were subjected to mass spectrometry analysis. 5 of the 6 protein bands analyzed by mass spectrometry displayed identical amino acid sequences to those predicted to be specified by 4 of the ORFs identified in the ϕEf11 genome. These included: ORF8 (predicted scaffold protein), ORF10 (predicted major head protein), ORF15 (predicted major tail protein), and ORF23 (presumptive antireceptor).